The Effect Of The Hypnoteaching Approach On Learning Motivation In Students In Class IVB MIN 1 Bantul 2021/2022 Academic Year - Muhammad Zuhri (Pedir Research Institut, 2021)
This study aims to determine the effect of the application of the hypnoteaching approach on the learning motivation of the Vb MIN 1 Bantul class students. This study uses a mixed methods approach, a type of method that combines qualitative and quantitative. Qualitative is used to find out how the hypnoteaching method is applied in the learning process and has a significant influence in increasing student learning motivation. While quantitative is used to find out how much influence the hypnoteaching approach can increase student learning motivation. The data collection is done by means of observation, interviews, and questionnaires. Data analysis techniques for making instruments, validity test, reliability test, and simple linear regression test. The results of this study show. First, the application of hypnoteaching in class IVb MIN 1 Bantul in the academic year 2021/2022 has a positive and significant influence in increasing student motivation. This is in line with the results of the analysis on qualitative data in the form of observation, interviews, and documentation. All these data indicate that students after getting a hypnoteaching approach to learning they feel happy, excited and learn more passionately. The steps are to use the relaxation of the eyes and all the nerves in the body. In addition, it is also implemented with steps of self-motivation, pacing-leading, positive and suggestive words, praise and modeling, yelling or shouting together, emotional hours, invitations and commands. Second This study uses mixed methods with 2 variables, one dependent variable that is learning motivation, and the independent variable is hypnoteaching. Both of these variables are made a questionnaire with each variable 30 statements. After testing the validity there are 4 invalid statements and must be issued. As long as the research instrument becomes 56 statements. Then the reliability test showed all the instruments of reliable research with Alpha above 0.7, which was 0.952. Then a simple linear regression test, with the result of R2 (coefficient of determination) 0.775, thus it can be said that the hypnoteaching approach has a very positive influence in increasing student learning motivation with an average percentage increase of 77.5%.